Analysis of Students' Mathematical Problem-Solving Ability on System of Linear Equations in Two Variables in Class VIII SMPN 3 Kisaran - Manalu, Pesta R; Rahmadani, Elfira; Masithoh, Ety (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research aims to determine the level of mathematical problem solving ability of class VIII-1 students at SMPN 3 Kisaran on the material of systems of linear equations in two variables (SPLDV). This research is a qualitative descriptive study with an instrument in the form of test questions consisting of 5 problem solving questions in the form of descriptions. The sample for this research was all students in class VIII-1 consisting of 32 students. This sample selection used a purposive sampling technique because the researcher had certain considerations so that the research subjects met the criteria desired by the researcher. Based on data analysis carried out regarding the level of students' mathematical problem solving abilities in the SPLDV material, it shows that the mathematical problem solving abilities of students in class VIII-1 SMPN 3 Kisaran fall into three categories, namely as follows: 6 students or 18.75% have problem solving abilities that are classified in the